2022
DOI: 10.12998/wjcc.v10.i4.1226
|View full text |Cite
|
Sign up to set email alerts
|

What are the self-management experiences of the elderly with diabetes? A systematic review of qualitative research

Abstract: BACKGROUND The number of elderly individuals with diabetes is dramatically increasing. Diabetes is a long-term condition and a noncommunicable disease and requires intensive daily self-management. Understanding of self-management from the patients’ perspectives is important to nurses, healthcare providers, and researchers and benefits people by improving their self-management skills. AIM To examine and synthesize qualitative studies that explore the experiences of elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 70 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…According to a study in Delhi, even though T2D is common in slums, it fails to be adequately understood, treated and controlled among the elderly 36. The results of a systematic review showed that there are five themes for diabetes self-management among elderly patients including the need for information on T2D care, support from the health system and social, functional decline, attitude of persons with T2D and challenges of adopting a healthy lifestyle 37. As a result, elderly patients need more financial, social and informational support from the health system, society and government.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study in Delhi, even though T2D is common in slums, it fails to be adequately understood, treated and controlled among the elderly 36. The results of a systematic review showed that there are five themes for diabetes self-management among elderly patients including the need for information on T2D care, support from the health system and social, functional decline, attitude of persons with T2D and challenges of adopting a healthy lifestyle 37. As a result, elderly patients need more financial, social and informational support from the health system, society and government.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, older adults are more likely to experience disease burden in dealing with physical and emotional symptoms, which is related to the contradictory information provided by multiple healthcare providers, 9 the possibility of functional decline, and whether there is an accessible support system. 10 To decrease the disease burden of diabetes in older adults, individualized interventions are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults diagnosed with diabetes need to perform regular daily management tasks such as considering meal timings, diet content, and daily injections, and to perform these tasks for the rest of their lives 7,8 . However, older adults are more likely to experience disease burden in dealing with physical and emotional symptoms, which is related to the contradictory information provided by multiple healthcare providers, 9 the possibility of functional decline, and whether there is an accessible support system 10 . To decrease the disease burden of diabetes in older adults, individualized interventions are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Older T2DM patients were found to have an accelerated decline in leg lean mass, muscle strength and functional capacity when compared with normoglycemic control groups ( 5 ). Evidence has shown that T2DM is an independent risk factor for functional limitations among the older population ( 6 ), impairing about 60% of activities of daily living (ADL) for diabetic people aged>65 years compared with only 34% for the same age group without T2DM in the USA ( 7 ), especially among older Mexican Americans with T2DM ( 8 ). Moreover, T2DM patients were two to three times more likely to suffer from disability than their counterparts ( 9 ), and utilized healthcare services more frequently as well.…”
Section: Introductionmentioning
confidence: 99%
“…Effective diabetes self-management is critical for maintaining health and preventing the occurrence of further diabetes-related complications such as diabetic ketoacidosis, hypoglycemia, cardiovascular diseases, retinopathy, nephropathy, vascular nephropathy, and foot complications ( 6 ). However, self-management can be especially challenging for elderly people with T2DM, as they are more likely to suffer from functional limitations and develop geriatric syndromes than those without diabetes ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%